Modulated electro-hyperthermia-enhanced liposomal drug uptake by cancer cells - Tsang, Yuk-Wah; Chi, Kwan-Hwa; Huang, Cheng-Chung; Chi, Mau-Shin; Chiang, Hsin-Chien; Yang, Kai-Lin; Li, Wen-Tyng; Wang, Yu-Shan (My University, 2019)
Purpose: Modulated electro-hyperthermia (mEHT) stands to be a significant technological advancement in the hyperthermia field, utilizing autofocusing electromagnetic power on the cell membrane to create massive apoptosis. Since mEHT possesses the unique ability to excite cell membranes, we hypothesized that mEHT could enhance the uptake of liposomal drugs by enhancing phagocytic activity. Materials and methods: Water bath control and mEHT were used to compare the enhancement of liposome-encapsulated doxorubicin (Lipodox (R)) uptake by cancer cells. Cancer cells were made visible by doxorubicin fluorescence to investigate drug uptake. Viable cell yield was determined via the Trypan Blue exclusion method. Various substrates were used to investigate the mechanism of drug-uptake enhancement. The murine colon carcinoma model, CT26, was used to confirm the tissue infiltration of Lipodox (R) and its therapeutic effect. Results: mEHT treatment showed a significant enhancement of Lipodox (R) uptake of doxorubicin fluorescence compared with 37 degrees C or 42 degrees C water bath treatment. Tumor tissue sections also confirmed that mEHT treatment achieved the highest doxorubicin concentration in vivo (1.44 +/- 0.32 mu g/g in mEHT group and 0.79 +/- 0.32 mu g/g in 42 degrees C water bath). Wortmannin was used to inhibit the macropinocytosis effect and 70 kDa dextran-FITC served as uptake substance. The uptake of dextran-FITC by cancer cells significantly increased after mEHT treatment whereas such enhancement was significantly inhibited by wortmannin. Conclusion: The result showed mEHT-induced particle-uptake through macropinocytosis. mEHT-enhanced uptake of Lipodox (R) may amplify the therapeutic effect of liposomal drugs. This novel finding warrants further clinical investigation.
Keywords: hyperthermia; cancer treatment; liposome; doxorubicin; micropinocytosis